Effect of Liquid Organic Fertilizer Concentration and NPK Fertilizer Dosage On the Growth and Yield of Pakcoy Plants (Brassica rapa L.) - Rachman, Redy; Amalia, Lia; Taryana, Yana (Institute of Computer Science (IOCS), 2022)
Pakcoy cultivation can not only be done on a large land, but for people who only have a narrow land such as urban communities can cultivate pakcoy using pots/polybags. Optimization of pakcoy plant production can be achieved when the need for macro and micro nutrients of the plant is met. By applying liquid organic fertilizer combined with inorganic fertilizer (NPK), it is hoped that it can increase plant productivity and efficiency in fertilizer use, so that the right formula is obtained between the mixture of liquid organic fertilizer and inorganic fertilizer (NPK). The experiment was carried out in Cibiru Wetan Village, Cileunyi District, Bandung Regency., 660-705 meters above sea level an order of Inceptisol soil, starting from October 2022 to November 2022. This study aims to study the interaction between the concentration of liquid organic fertilizer and the amount of inorganic fertilizer (NPK) on the growth and yield of pakcoy plants and to determine the optimal concentration of liquid organic fertilizer at each dose of inorganic fertilizer (NPK). The results of the experiment showed that there was an interaction between POC concentration and NPK dosage on plant height and leaf count, 15 HST, 20 HST and 25 HST, and no interaction occurred in plant height 10 HST, leaf count 10 HST, fresh weight, fresh plant yield weight, dry weight and NPA